Formulation and optimisation of lamivudine‐loaded Eudragit® S 100 polymer‐coated pectin microspheres for colon‐specific delivery - Satheesh Vilas; Sivasudha Thilagar (IET Nanobiotechnology)
Abstract This investigation is to find a prolonged or delayed drug release system, exclusively for the treatment of hepatitis‐B to reduce the side effects, which arise when conventional solid dose forms are administered. To pursue this goal, lamivudine‐loaded Eudragit‐coated pectin microspheres have been formulated employing water/oil (W/O) emulsion evaporation strategy. The formulation was optimised using a 34 factorial design. A drug to polymer ratio of 1:2, the surfactant of 1 ml, the volume of 50 ml of processing medium with a stirring speed of 2500 rpm were found to be the optimal parameters to obtain the lamivudine‐loaded Eudragit‐coated pectin microspheres formulation with a high drug entrapment efficiency of 89.44% ± 1.44%. The in vitro release kinetics of lamivudine was a suitable fit to the Higuchi model, indicating a diffusion‐controlled release with anomalous transport. The obtained microspheres were then subjected to different characterisation studies, including scanning electron microscopy (SEM), Fourier transform infrared spectroscopy (FTIR), differential scanning calorimetry (DSC), and X‐ray diffraction (XRD). The results of this study clearly indicate that Eudragit‐coated pectin microspheres could be the promising controlled release carriers for colon‐specific delivery of lamivudine in the presence of rat cecal content.